Ginsenoside Rb1 Induces Beta 3 Adrenergic Receptor–Dependent Lipolysis and Thermogenesis in 3T3-L1 Adipocytes and db/db Mice - Lim, Seona; Park, Jinbong; Um, Jae-Young (Frontiers in Pharmacology, 2019)
Obesity is constantly rising into a major health threat worldwide. Activation of brown-like transdifferentiation of white adipocytes (browning) has been proposed as a promising molecular target for obesity treatment. In this study, we investigated the effect of ginsenoside Rb1 (Rb1), a saponin derived from Panax ginseng Meyer, on browning. We used 3T3-L1 murine adipocytes and leptin receptor mutated db/db mice. The lipid accumulation, AMP-activated protein kinase alpha (AMPKα)-related pathways, lipolytic and thermogenic factors were measured after Rb treatment in 3T3-L1 adipocytes. Body weight change and lipolysis-thermogenesis factors were investigated in Rb1-treated db/db mice. Beta 3 adrenergic receptor activation (β3AR) changes were measured in Rb1-treated 3T3-L1 cells with or without β3AR inhibitor L748337 co-treatment. As a result, Rb1 treatment suppressed lipid accumulation and decreased lipid droplet size in 3T3-L1 adipocytes. Rb1 also induced phosphorylations of AMPKα pathway and sirtuins. Moreover, lipases and thermogenic factors such as uncoupling protein 1 were increased by Rb1 treatment. Through these results, we could expect the non-shivering thermogenesis program can be induced by Rb1. In db/db mice, 6-week-injection of Rb1 resulted in decreased inguinal white adipose tissue (iWAT) weight associated with shrinked lipid droplets and increased lipolysis and thermogenesis. The thermogenic effect of Rb1 was possibly due to β3AR, as L748337 pre-treatment abolished the effect of Rb1. In conclusion, we suggest Rb1 as a potential lipolytic and thermogenic therapeutic agent which can be used for obesity treatment.